2013
DOI: 10.1590/0037-8682-0190-2013
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole and amphotericin-B resistance are associated with increased catalase and superoxide dismutase activity in Candida albicans and Candida dubliniensis

Abstract: Introduction:Candida dubliniensis, a new species of Candida that has been recovered from several sites in healthy people, has been associated with recurrent episodes of oral candidiasis in AIDS and HIV-positive patients. This species is closely related to C. albicans. The enzymatic activity of C. dubliniensis in response to oxidative stress is of interest for the development of drugs to combat C. dubliniensis. Methods: Fluconazole-and amphotericin B-resistant strains were generated as described by FeketeForgác… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 35 publications
4
30
1
1
Order By: Relevance
“…Given that different strains had different antioxidant capacity, mainly reflected in the activities of antioxidant enzymes, we suggested that the T. asahii clinical group stains may have higher antioxidant capacity than the environment group strains. According to previous studies, we also obtained that the mean SOD activity of Clinical group strains of T. asahii (10.45 ± 3.87 U/mg) was equivalent to that of Cryptococcus (12 ± 0.5 U/mg) [16], and below that of Candida dubliniensis (27.87 ± 20.82 U/mg) [15], significantly lower than that of C. albicans (151.8 ± 73.27 U/mg) [15]. The mean catalase activity of T. asahi Clinical group strains (48.51 ± 7.60 U/ mg) was significantly higher than that of A. fumigatus (1.75 ± 0.75 U/mg), Aspergillus terreus (3.5 ± 0.8 U/mg) [17].…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Given that different strains had different antioxidant capacity, mainly reflected in the activities of antioxidant enzymes, we suggested that the T. asahii clinical group stains may have higher antioxidant capacity than the environment group strains. According to previous studies, we also obtained that the mean SOD activity of Clinical group strains of T. asahii (10.45 ± 3.87 U/mg) was equivalent to that of Cryptococcus (12 ± 0.5 U/mg) [16], and below that of Candida dubliniensis (27.87 ± 20.82 U/mg) [15], significantly lower than that of C. albicans (151.8 ± 73.27 U/mg) [15]. The mean catalase activity of T. asahi Clinical group strains (48.51 ± 7.60 U/ mg) was significantly higher than that of A. fumigatus (1.75 ± 0.75 U/mg), Aspergillus terreus (3.5 ± 0.8 U/mg) [17].…”
Section: Discussionsupporting
confidence: 62%
“…At the 9th generation of reply induction, the mean SOD activity of strains was 3.53 ± 0.84 U/mg, the mean catalase activity was 47.15 ± 25.88 U/mg. These results implied that fluconazole may simulate or induce the expression of antioxidant enzymatic activity of T. asahii, leaving the antioxidant capacity of these strains further promoted [15]. Because that the activities of SOD and catalase in T. asahii could go down to normal level without fluconazole exposure, we suggested that the induction of antioxidant enzymatic activity may be regulatory [1].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations